The “Black Question” Clarified by the Long History of French Colonialism - (:unkn) unknown (My University, 2007)
The history of the relationship between France and Africa during the colonial and postcolonial periods demonstrates permanent ambiguity: the elites in particular, though adopting as a matter of course a critical attitude towards colonialism, at the same time supported the French model of assimilation. Changes occurred when immigration from Africa was stopped. From then on, resentment grew, as much among the Africans as among the French descendants of African immigrants, thus giving birth to the “Black issue”.
Keywords: African Research